Characterization of some indigenous breeds of chicken in Kalahandi and Nuapada Districts of Odisha - N S MAJHI; S C MISHRA; N PANDA; P K MISHRA (Indian Journal of Animal Sciences, 2014)
The present study was aimed to identify and characterize 3 different domestic breeds of chicken in 2 tribal dominant districts of Odisha. According to the colour pattern and local name these 3 breeds are named as Kabri, Chitri and Khairi which are found different from avian chicken breeds described so far in their phenotypic characters as well as in the performance traits. All these avian species studied in this investigation are raised in smallholder production system. The phenotypic traits like comb type, plumage colour, plumage pattern and information on body length, body girth, shank length, breast angle, keel length measurements etc. were studied. Attempt was also made to evaluate its performance traits like growth rate, body weight, egg production in these 3 breeds.